An Empirical Analysis of the Relationship Between Organizational Climate, Teacher’s Performance, and Student’s Achievement - Abdul Wahid; Prof. Dr. Shahida Sajjad; Dr. Sadia Siddique (Dialogue Social Science Review (DSSR), 2025)
This study, conducted in public secondary schools of Quetta, Baluchistan, examined the relationships between organizational climate, teacher job performance, and student academic achievement. Employing a descriptive survey design with stratified random sampling, data were collected from 50 school administrators, 648 teachers, and 375 students using validated questionnaires. Statistical analyses, including Pearson's correlation, ANOVA, and regression, demonstrated a strong positive correlation (r = 0.986, p < 0.01) between organizational climate and teacher job performance and a moderate positive correlation (r = 0.319, p = 0.024) with student achievement. Regression analysis showed that organizational climate significantly predicted teacher job performance (F (1, 696) = 24757.519, p < 0.001) and student achievement (F(1, 48) = 5.453, p = 0.024). These findings suggest that strategic efforts to enhance school climate can yield significant improvements in teacher effectiveness and contribute to positive student outcomes, offering valuable insights for educational stakeholders in resource-constrained environments.